HPV vaccine behaviors and intentions among a diverse sample of women aged 27-45 years: implications for shared clinical decision-making - Jennifer D. Allen; Nadia N. Abuelezam; Raviv Rose; Katelin Isakoff; Gregory Zimet; Holly B. Fontenot (BMC, 2024)
Abstract Background The Advisory Committee on Immunization Practices issued a shared clinical decision-making (SCDM) recommendation for HPV vaccination in persons aged 27-45. Since expanded eligibility for the vaccine was issued, little information has been available about HPV vaccine behaviors and intentions among women in this age group. Methods We conducted a cross-sectional online survey among women aged 27-45 years recruited through a Qualtrics™ respondent panel (N = 324) to answer the following questions (1) What is the prevalence of HPV vaccination among a diverse sample of adult women aged 27-45 years? (2) What are the characteristics of those who have or have not previously been vaccinated? and (3) What factors are associated with the intention to obtain the HPV vaccine among those who had never been vaccinated? Multivariable logistic regression analyses estimated adjusted odds ratios (AORs) and 95% confidence intervals (95% CIs). Results Only 31.1% had at least one dose of the HPV vaccine. In multivariable analyses, those more likely to have been vaccinated were younger and were more likely to believe that the vaccine was effective. Of those unvaccinated or unsure, 54.8% indicated they were likely to get vaccinated in the future. Factors associated with future vaccine intention (compared to those not intending) included beliefs about vaccine testing, perceived likelihood of HPV infection, greater comfort in asking one's provider for vaccination, and prior negative healthcare experiences. Conclusions Our findings suggest that many women in this age group are interested in HPV vaccination. While the recommendation is for SCDM rather than routine vaccination for all women in this age group, efforts to promote informed decision-making among mid-adult women may include educating women about the rigorous vaccine testing and approval process, their risk factors for HPV infection, and encouraging them to engage in SCDM with their medical providers. Targeted efforts to reach women who have had negative experiences with healthcare may also be needed.